Molecular and genetic studies of the predisposition to the development of psoriasis among the population of the Russian Federation: a study of polymorphisms of TNFAIP3, TNIP1, TYK2 and REL genes - A. A. Kubanov; A. A. Mineyeva (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Goal. To study the role of polymorphic variants of genes encoding proteins of the signaling pathway of the nuclear transcription factor kappa-B, NF-kB (TNFAIP3 (rs610604), TNIP1 (rs17728338), TYK2 (rs12720356) and REL (rs702873)) in the predisposition to psoriasis among the Caucasian population of the Russian Federation. Materials and methods. The authors studied markers of the predisposition to the development of psoriasis such as TNFAIP3 (rs610604), TNIP1 (rs17728338), TYK2 (rs12720356) and REL (rs702873) using Real-Time PCR methods and allele-specific oligonucleotide probes and PFLP (Restriction Fragment Length Polymorphism) assay in whole blood samples taken from psoriatic patients (n = 301). To compare the frequency of genotypes, the authors used data obtained as a result of the genotyping of DNAs taken from healthy volunteers (n = 109). Results. The authors analyzed particular features of the distribution of polymorphic variants of TNFAIP3 (rs610604), TNIP1 (rs17728338), TYK2 (rs1272035) и REL (rs702873) genes in a sample of 301 psoriatic patients and 109 healthy volunteers from the Russian Federation. They revealed reliable differences in the frequency of registration of genotypes of these genes. The authors also determined genotypes considered as risk factors with regard to the development of psoriasis (TNFAIP3-A/C, TNIP1-A/G, TNIP1-A/A and TYK2-T/T) as well as protector genotypes (TNFAIP3-A/Ä, REL-A/A and TYK2-T/G)